Lucky stuff [compact disc, unabridged] - Fiffer, Sharon Sloan, 1951- (Dreamscape Media, 2012)
With her divorce final, Jane must clear out her antique collection and sell her house. Now homeless, Jane heads to her hometown in Illinois to find it, too, has been turned upside-down. Lucky Miller, a little-known comedian, is staging a comeback. Suspicious, Jane's mother Nellie hires Jane to investigate. Still, Nellie may be the least of Lucky's problems when a driver on his crew turns up dead hours after claiming that Lucky tried to kill him.